PENGARUH DESAIN PRODUK DAN KUALITAS PRODUK TERHADAP LOYALITAS PELANGGAN DENGAN KEPUASAN SEBAGAI VARIABEL INTERVENING PENGGUNA HP OPPO (STUDY KASUS DI PESANTREN MIFTAHUL HUDA KEPANJEN-MALANG) - Abdurahman Abdurahman; Rois Arifin; M. Hufron (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACTThis research I’m made to know and analyse the effect of product design and product quality towards customer loyalty with customer satisfaction as intervening variable. This research is a quantitative research by using path analysis technique. Sample taken by using Slovin formula with using the purposive sampling technique with 94 sample of respondence.The result shows that there is the significant effect of product design towards customer satisfaction, there is significant effect of product quality towards customer satisfaction, product design also have a significant effect towards customer loyalty, product quality affected on customer loyalty, satisfactory have significant effect towards customer loyalty. Then, indirectly product design have affected towards customer loyalty by the satisfactory as intervening variable cannot be proven, product quality indirectly affected on customer loyalty with satisfactory as intervening variable. Based on the result of this research can be concluded that one product which have interesting design and good quality can make the customer feels satisfied, so that customer will be loyal.Keywords: Product Design, Product Quality, Customer Loyalty And Satisfactory